Personal photograph album (1890)
Uncaptioned photographs of officers of the British Army in India; groups in theatrical costume; scenes and buildings; also included are 12 watercolour drawings.
Inscription of first leaf: K M F, Col. Henry Fraser.
Keywords: Great Britain. -- Army. -- Colonial forces -- India; Soldiers -- India; India -- Pictorial works